2022
DOI: 10.30598/jupitekvol5iss1pp23-33
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ethnomathematics Based Learning on Mathematics Problem-Solving Ability: A Meta-Analysis

Abstract: The introducer of ethnomathematics defined ethnomathematics as mathematics practised among identified cultural groups. Ethnomathematics positively impacts the learning process either as a Moderate or an approach to, for example, problem-solving ability. Previous researchers have carried out several studies on implementing ethnomathematical-based learning to improve students’ problem-solving ability. However, the analysis shown is very varied, so it still raises doubts about the impact of learning using ethnoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…These results indicate that the research year variable affects the effectiveness of applying ethnomathematics-based learning to the mathematical abilities of elementary school students. This finding is also consistent with the research of Apriatni et al (2022) who found that the application of ethnomathematics-based learning was reported to be most effective in 2021-2022 compared to 2015-2016, 2017-2018, and 2019-2020. 98 In addition, a meta-analysis study by Purnomo et al 99 and Samritin et al 100 also found that the variable year of publication affects the effect size.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that the research year variable affects the effectiveness of applying ethnomathematics-based learning to the mathematical abilities of elementary school students. This finding is also consistent with the research of Apriatni et al (2022) who found that the application of ethnomathematics-based learning was reported to be most effective in 2021-2022 compared to 2015-2016, 2017-2018, and 2019-2020. 98 In addition, a meta-analysis study by Purnomo et al 99 and Samritin et al 100 also found that the variable year of publication affects the effect size.…”
Section: Resultssupporting
confidence: 92%
“…These results indicate that the sample size variable does not affect the effectiveness of applying ethnomathematics-based learning to the mathematical abilities of elementary school students. Apriatni et al (2022) also reported that ethnomathematicsbased learning was effective on problem solving abilities at sample sizes ≤ 30 and > 30, but had insignificant differences. 97 The consistency of these findings provides a more accurate conclusion.…”
Section: Resultsmentioning
confidence: 94%